The Influence of the Cooperative Script Method on Students' Short Story Writing Ability - Marzuki, Nayla Alfia (Trigin Institute, 2025)
This research examines the impact of the Cooperative Script method on students' short story writing abilities. The Cooperative Script method, a collaborative learning strategy, was implemented with a group of secondary school students to enhance their creativity, narrative skills, and overall writing quality. The study involved an experimental group (n=30) that participated in the Cooperative Script method and a control group (n=30) that received traditional writing instruction. Data were collected through pre- and post-intervention writing assessments, which were evaluated based on creativity, structure, and language use. The results indicate a significant improvement in the writing abilities of students in the experimental group, demonstrating that collaborative learning fosters creativity and enhances narrative skills. These findings suggest that the Cooperative Script method can be an effective tool for improving short story writing skills, promoting peer interaction, and fostering a more engaging and supportive learning environment. However, the study's limitations, including a small sample size and short intervention duration, indicate the need for further research to explore the long-term effects and broader applicability of this approach in various educational settings.